A3.9 IGG subclasses of autoantibodies directed against the angiotensin receptor type 1 and the endothelin receptor type a and their clinical relevance. (31st January 2014) - Günther, J.; Kill, A; Becker, M.; Siegert, E; Heidecke, H; Riemekasten, G
Abstract : Background and Objectives: IgG4-related diseases are often characterised by a generalised inflammatory fibrosis which is also present in patients suffering from systemic sclerosis (SSc). Recent findings indicate the importance of autoantibodies (Aabs) against the angiotensin II type-1 receptor (AT1R) and the endothelin type-A receptor (ETAR) in the pathogenesis of SSc. Therefore, we analysed the levels of anti-AT1R/ETAR IgG sublasses in patients with SSc to determine a possible role of IgG subclasses as markers for disease manifestations in SSc. Material and Methods: Sera from 91 SSc patients, 59 patients suffering from systemic lupus erythematosus (SLE), and from 199 healthy donors were analysed for the levels of anti-AT1R and anti-ETAR Aabs as well as for the different anti-AT1R and anti-ETAR IgG subclasses by ELISA. The results were associated with clinical manifestations using Mann-Whitney test and correlated with the time since onset of disease manifestations by Spearman correlation test. Results: IgG3 followed by IgG1 was found to show highest anti-AT1R/ETAR Aab levels in all analysed groups, in which SSc patients as well as SLE patients had higher IgG1 and IgG3 anti-AT1R/ETAR Aab levels as compared to healthy donors. Comparing SLE and SSc patients IgG1 and IgG3 showed slightly higher anti-AT1R/ETAR Aab levels in SLE. Within the SSc group patients with diffuse SSc had higher anti-AT1R/ETAR IgG3 levels as compared to those with limited disease or overlap forms. Correlation analysis with SSc-related clinical manifestations revealed that levels of anti- AT1R/ETAR IgG3 negatively correlated with time since onset of Raynaud's phenomenon, and with time since first detection of PAH. Of note, there were negative correlations between levels of anti-AT1R/ETAR IgG3 levels and diffusion capacity for carbon monoxide (DLCO) as well as between anti-AT1R/ETAR-IgG3 levels and forced vital capacity (FVC) values (p = 0.02/0.07 and p = 0.01/0.03, respectively). Conclusion: Interestingly, not IgG4 but IgG3 showed highest anti-AT1R/ETAR Aab levels when compared to other IgG subclasses. However, in SSc patients, anti-AT1R/ETAR IgG3 levels are strongly correlated to certain disease manifestations, whereby high anti-AT1R/ETAR IgG3 levels are associated with low DLCO and FVC indicating deterioration of lung function. According to these findings high anti-AT1R/ETAR IgG3 levels could predict for lung function deterioration and represent a new marker for SSc complications.